Japanese Evidences on Nerve-Preserving Lateral Pelvic Lymh Node Dissection for Rectal Cancer - Kanemitsu, Yukihide; Shida, Dai; Tsukamoto, Shunsuke; Moritani, Konosuke; Sakamoto, Ryohei (Clinics in Colon and Rectal Surgery, 2020)
In Japan, the standard treatment for advanced low rectal cancer has been total mesorectal excision (TME) + lateral pelvic lymph node dissection (LLND). On the other hand, in the West, preoperative chemoradiotherapy (CRT) + TME has been established as the standard. Japanese surgeons developed nerve-preserving LLND that could reduce complications associated with extended dissection. The Japan Clinical Oncology Group (JCOG)0212 trialinvestigated on the outcomes of so-called prophylactic LLND in patients without evident lateral lymph node metastasis in preoperative diagnostic imaging. Data from the JCOG0212 trial demonstrated scientific validity of the theory and practice of the Japanese approach. Data from the JCOG0212 trial supported the validity and safety of the Japanese approach, that is, TME + LLND for low rectal cancer without routine use of preoperative CRT. For future direction, modern approach for rectal cancer should involve both of the Eastern and Western strategies by combining LLND and CRT.
Keywords: rectal cancer; lateral lymph node dissection; total mesorectal excision